Higher Dimensional P - Path Route Minimum Distance Supply To The Destinations From The Central Station - Reddy P, Madhu Mohan; P, Jayalakshmi; Kanth V, Rajani (Journal of Neonatal Surgery, 2025)
We take into consideration one of the non-linear polynomial combinatorial programming issues known as P-path route minimum distance supply to the destinations from the central station.The distance matrix D(i, j, k) is given from the i th destination to the jth destination utilizing the k th facility, and there are n destinations. A facility, denoted by the letter K, can be an individual component that affects travel distances or costs. Depending on the needs of the many destinations, the central station has the potential to supply the load. The challenge is to determine the lowest distance, while taking the aforementioned factors into account, to connect all of the destinations to the central station (let’s say one). We created a Pattern Recognition Technique based Lexi Search Method for this issue, and we built the suggested algorithm in C. We compared it to the models already in use and came to the conclusion that it was recommended for handling higher dimensional issues.